Network Structures in the Regional Industry - Korovin, Grigoriy B. (Economy of Regions, 2020)
Rapid digitalisation of the economy introduces network forms of coordination of industrial enterprises activities. A network approach to cooperation in the industrial sector requires the development of theoretical foundations and methodological approaches, considering the specificity of industrial territories. The study uses various methods: structural and dynamic analysis of regional statistics and open data of industrial enterprises and regional network structures, expert commentary, development analysis of network structures in the industrial regions. The research identified possible network changes in the traditional industrial business models. Due to such changes, partners and consumers are involved in the product creation, customisation, individualisation, and price determination based on network information services. A new typology includes four types of structures corresponding to four quadrants of a two-dimensional matrix, divided by the strategic goals of merging organisations and the network structure functions. The selected types include associations of the producers of homogeneous products; partnerships and alliances; local networks; supply and value chains. The empirical part of the paper involves the identification and analysis of four types of network structures in the Sverdlovsk region and an assessment of their significance to the economy. Finally, the study assessed the development dynamics of regional network structures using particular indicators. The results can be used for developing the concept of network economy, creating tools for managing the network industry, and establishing a new industrial policy that takes into account a network aspect of cooperation.